2023
DOI: 10.3389/fimmu.2023.1203539
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation and immunity in non-small cell lung cancer: a new era of cryo-immunotherapy

Antonio Velez,
Andrew DeMaio,
Daniel Sterman

Abstract: Despite remarkable advances in tumor response and patient survival in the past decade, systemic immunotherapies for lung cancer result in an objective response in only around half of patients treated. On the basis of this limitation, combination strategies are being investigated to improve response rates. Cryoablation has been proposed as one such technique to induce immunogenic cell death and synergize with systemic immunotherapies, including immune checkpoint inhibitors. Cryoablation has been traditionally d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…CA is known to be immunomodulatory as a monotherapy [80][81][82], and NSCLC has been shown to respond to immune activation [83,84]. Indeed, there are a growing number of studies investigating the use of immune checkpoint inhibitors (ICIs) and other targeted immunotherapy molecules in lung cancer [45,85]. Additionally, a study by Gravett et al (2019) found that subcytotoxic concentrations of chemotherapeutic drugs, including gemcitabine, upregulated CD95/FAS death receptors and NKG2D ligands in A549 cells, suggesting a sensitization pathway for immune activation [86].…”
Section: Discussionmentioning
confidence: 99%
“…CA is known to be immunomodulatory as a monotherapy [80][81][82], and NSCLC has been shown to respond to immune activation [83,84]. Indeed, there are a growing number of studies investigating the use of immune checkpoint inhibitors (ICIs) and other targeted immunotherapy molecules in lung cancer [45,85]. Additionally, a study by Gravett et al (2019) found that subcytotoxic concentrations of chemotherapeutic drugs, including gemcitabine, upregulated CD95/FAS death receptors and NKG2D ligands in A549 cells, suggesting a sensitization pathway for immune activation [86].…”
Section: Discussionmentioning
confidence: 99%
“…In lung tumors, cryoablation is typically conducted with the guidance of CT scans, accompanied by sedation and local anesthesia [ 125 ]. The procedure can be performed via endobronchial, direct intrathoracic, or percutaneous routes, depending on the location and size of the tumor [ 127 ]. Some adverse effects faced by lung cancer patients include mild complications such as bleeding, pneumothorax, and pulmonary infection [ 125 ].…”
Section: Cryoablationmentioning
confidence: 99%
“…A promising strategy involves combining cryoablation with immunotherapy; however, cryosurgery alone cannot elicit a robust immunotherapeutic response to cancer [ 126 ]. The administration methods for combining cryoablation with immunotherapy include percutaneous and bronchoscopic approaches [ 127 ]. Clinical trials were carried out to explore the effectiveness of combining cryosurgery with allogeneic NK cell immunotherapy for treating NSCLC.…”
Section: Cryoablationmentioning
confidence: 99%
“…Cryoablation is a technique in which the tissue is exposed to multiple freeze-thaw cycles (usually to À40 8C) to induce direct cellular injury and thrombosis of the vascular structures that feed the tumor [26]. Cryoablation can be performed via percutaneous or bronchoscopic approach.…”
Section: Cryoablationmentioning
confidence: 99%